LTE security - Forsberg, Dan (Wiley, 2010)
"The book will address the security architecture for SAE/LTE, which is based on elements of the security architectures for GSM and 3G, but needed a major redesign due to the significantly increased complexity, and different architectural and business requirements of fourth generation systems. The book will present the requirements and will explain in detail the security mechanisms employed to meet these requirements. The specifications generated by standardization bodies only inform about how to implement the system (and this only to the extent required for interoperability), but almost never inform readers about why things are done the way they are. Furthermore, specifications tend to be readable only for a small group of experts and lack the context of the broader picture. The proposed book is intended to fill this gap by providing first hand information from insiders who participated in decisively shaping SAE/LTE security in the relevant standardization body, 3GPP, and can therefore explain the rationale for design decisions in this area. Contents include: 2G security (GSM); 3G security (UMTS); 3G-WLAN interworking; SAE/LTE security; Security for Voice over LTE / IMS; Security for home base station deployments; Outlook/future challenges."--